Coaching Approach: Empowering Team Work For Organizational Transformation: Human Resource Management - Candra Susanto, Primadi; Suhendra, Agus; Sundari, Pipit; Trisna Wijayanthi, Ida Ayu; Fachrial, Peppy (International Journal of Advanced Multidisciplinary, 2024)
Abstract: The purpose of this literature research is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The literature review research article on the training approach: empowering teamwork towards organizational transformation is a scientific literature article in the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Sage, WoS, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. The results of this literature review article are: 1) Coaching has an effect on Organizational Transformation; 2) Mentoring has an effect on Organizational Transformation; 3) Team Empowerment has an effect on Organizational Transformation; and 4) Delegation Leadership has an effect on Organizational Transformation. Keyword: Organizational Transformation, Coaching, Mentoring, Team Empowerment, Delegation Leadership